Coarse-Grained Simulations Complemented by Atomistic Molecular Dynamics Provide New Insights into Folding and Unfolding of Human Telomeric G-Quadruplexes - Stadlbauer, Petr; Mazzanti, Liuba; Cragnolini, Tristan; Wales, David J; Derreumaux, Philippe; Pasquali, Samuela; Šponer, Jiří (Journal of chemical theory and computation, 2016)
G-quadruplexes are the most important noncanonical DNA architectures. Many quadruplex-forming sequences, including the human telomeric sequence d(GGGTTA)n, have been investigated due to their implications in cancer and other diseases, and because of their potential in DNA-based nanotechnology. Despite the availability of atomistic structural studies of folded G-quadruplexes, their folding pathways remain mysterious, and mutually contradictory models of folding coexist in the literature. Recent experiments convincingly demonstrated that G-quadruplex folding often takes days to reach thermodynamic equilibrium. Based on atomistic simulations of diverse classes of intermediates in G-quadruplex folding, we have suggested that the folding is an extremely multipathway process combining a kinetic partitioning mechanism with conformational diffusion. However, complete G-quadruplex folding is far beyond the time scale of atomistic simulations. Here we use high-resolution coarse-grained simulations to investigate potential unfolding intermediates, whose structural dynamics are then further explored with all-atom simulations. This multiscale approach indicates how various pathways are interconnected in a complex network. Spontaneous conversions between different folds are observed. We demonstrate the inability of simple order parameters, such as radius of gyration or the number of native H-bonds, to describe the folding landscape of the G-quadruplexes. Our study also provides information relevant to further development of the coarse-grained force field.
Keywords: simulace molekulární dynamiky; G-kvadruplexy; teplota; termodynamika; Kinetics; Nucleic Acid Conformation; Telomere; Thermodynamics; Humans; telomery; lidé; Molecular Dynamics Simulation; Temperature; kinetika; obrácené repetice; G-Quadruplexes; konformace nukleové kyseliny; Inverted Repeat Sequences